2007
DOI: 10.2527/jas.2006-721
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunity in pigs with high and low responses to porcine reproductive and respiratory syndrome virus infection1,2

Abstract: ABSTRACT:One hundred Hampshire × Duroc crossbred pigs (HD) and 100 NE Index line (I) pigs were infected with porcine reproductive and respiratory syndrome (PRRS) virus and evaluated for resistance/susceptibility. Controls (100/line) were uninfected littermates to the infected pigs. Viremia, change in weight (WT⌬), and rectal temperature at 0, 4, 7, and 14 d postinfection were recorded. Lung, bronchial lymph node (BLN), and blood tissue were collected at necropsy (14 d postinfection). The first principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 27 publications
5
45
0
Order By: Relevance
“…This was investigated in a recent study (Petry et al, 2007), which compared expression levels of 11 immune genes involved in innate and adaptive immunity between pigs classified as high and low responders to PRRSV according to clinical and lesions symptoms from the HD and NEI lines used in their previous studies. The authors found that expression levels of IL-1β and IL-6 in the serum, lung, and bronchial lymph node were indeed greater for the leaner HD pigs than for pigs from the NEI line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was investigated in a recent study (Petry et al, 2007), which compared expression levels of 11 immune genes involved in innate and adaptive immunity between pigs classified as high and low responders to PRRSV according to clinical and lesions symptoms from the HD and NEI lines used in their previous studies. The authors found that expression levels of IL-1β and IL-6 in the serum, lung, and bronchial lymph node were indeed greater for the leaner HD pigs than for pigs from the NEI line.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus infection is commonly known to have a negative impact on growth, but the degree of the impact appears to vary between and within pig lines or breeds (Greiner et al, 2000;Petry et al, 2005Petry et al, , 2007 The underlying mechanisms for this relationship are still poorly understood. It can be envisaged that genetic resistance to PRRSV may influence performance in positive (e.g., less impact of the virus on the biological systems) and negative (e.g., the resistant animal diverts more resources and effort to the immune mechanisms rather than growth) ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these systems display large interindividual variations, partly attributable to genetic background. In pigs, breed-related differences have been observed for basal and stress-induced secretion of cortisol and adenocorticotropic hormone (Dé sauté s et al, 1999;Dé sauté s et al, 2002), acute-phase protein production -E-mail: Elodie.Merlot@rennes.inra.fr (Clapperton et al, 2007), leukocyte blood numbers (Clapperton et al, 2005a), antibody-and cell-mediated immune responses (Joling et al, 1993;Wilkie and Mallard, 1999) and susceptibility to several viruses (Opriessnig et al, 2006;Vincent et al, 2006;Petry et al, 2007). This variability was shown to rely on the additive genetic effects of a few quantitative trait loci (EdforsLilja et al, 2000;Wimmers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, controlled genetic studies on susceptibility to specific diseases are difficult to conduct due to size and cost limitations resulting in restrictions on pigs per line and breed. It is well known that genetic components in disease resistance exist in pigs such as reported with porcine reproductive and respiratory syndrome virus (Halbur et al, 1998;Petry et al, 2005Petry et al, , 2007Vincent et al, 2006), pseudorabies virus (Reiner et al, 2002), Salmonella sp. (Wigley, 2004), and Escherichia coli (Duchet-Suchaux et al, 1991;Michaels et al, 1994).…”
Section: Introductionmentioning
confidence: 99%